2021
DOI: 10.1109/jstars.2021.3065399
|View full text |Cite
|
Sign up to set email alerts
|

iSEAM: Improving the Blooming Effect Adjustment for DMSP-OLS Nighttime Light Images by Considering Spatial Heterogeneity of Blooming Distance

Abstract: The longest archive makes DMSP-OLS nighttime light (NTL) images unparalleled in relevant time series studies. However, these studies have been constrained by the blooming effect. The self-adjusting model (SEAM) proposed in 2019 solves this problem to some extent. However, SEAM assumed all pixels in NTL images with a constant blooming distance 3.5 km. In fact, the blooming distance is related to the land covers and the brightness of artificial lights. This assumption leads to large errors in cities that have bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The final result was obtained by subtracting the brightness value caused by the blooming impact from the original brightness value. To alleviate saturation’s influence on blooming effect correction, we performed the saturation effect correction before blooming effect correction on DMSP-OLS NTL images 27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final result was obtained by subtracting the brightness value caused by the blooming impact from the original brightness value. To alleviate saturation’s influence on blooming effect correction, we performed the saturation effect correction before blooming effect correction on DMSP-OLS NTL images 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Zhuo et al . 27 proposed an improved SEAM model (iSEAM) considering spatial heterogeneity of effective blooming distance while introducing land cover data. Based on the above methods, some global or regional NTL data products were generated to overcome one or more of these problems 14 , 28 31 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Using the interference data acquired by the InGaAs detector [5] applied to atmospheric CO2 concentration detection as the research object, unlike the "overflow phenomenon" observed when CCD pixels were saturated [6], the responses of the individual pixels of the InGaAs detector do not interfere with each other. Without considering the nonlinear response of pixels near saturation values, traditional detectors' saturation value corrections often use linear or nonlinear fitting methods [7]. These methods fit the non-saturation value changes near the saturation value to predict the saturation value but lack a physical explanation for the detection system.…”
Section: Introductionmentioning
confidence: 99%
“…The success of DMSP-OLS also promoted the development of new generation nighttime light platforms and products, such as Suomi National Polar-Orbiting Partnership-Visible Infrared Imaging Radiometer (NPP-VIIRS), EROS-B, Aerocube-5, CUMULOS, Luojia 1-01, and Jilin-1. Although these new data have advantages in portraying urban spatial morphology and structures with high spatial and temporal resolutions [11]- [13], the DMSP-OLS nighttime light data, especially the nighttime stable light (NSL) products remain irreplaceable for many studies such as the study of the urbanization process, because it has the longest time span in currently available nighttime light data sources [14], [15]. However, the NSL time-series product suffers from inconsistency problem, i.e., the image data of different years cannot be compared with each other directly, due to shortcomings of the OLS sensors, such as lack of on-board calibration, the presence of the saturation effect [16]- [18], and being carried on different satellite platforms [19].…”
mentioning
confidence: 99%